Domination and power domination in a one-pentagonal carbon nanocone structure - Pandian, Shoba; N., Mohana (Frontiers in Chemistry, 2024)
Domination is an important factor in determining the robustness of a graph structure.A thorough examination of the graph's topological structure is necessary for analyzing and examining the graph for various aspects. Understanding the stability of a chemical compound is a significant criterion in chemistry that necessitates conducting numerous experimental tests. The domination number and power-domination number are pivotal in defining a wide range of physical properties, which include physiochemical properties, thermodynamic properties, chemical activities, and biological activities. The one pentagonal carbon nanocone (1-PCNC) is a member of the carbon nanocone family and has a similar structure to that of honeycomb networks, which are renowned for their robustness. In this paper, we find the domination number and power domination number of 1-PCNC by considering it as an (m-1)-layered infinite graph.